DAMPAK MATA KULIAH KEWIRAUSAHAAN TERHADAP MINAT MAHASISWA UNTUK BERWIRAUSAHA SETELAH LULUS KULIAH PADA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS PEKALONGAN - Dwi Susilo; Kartono Muhammad (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
The Impact of Entrepreneurship Course to The Students  Interest as an Entrepreneur  After Graduation Lecture in   Management Program, Economic Faculty of Pekalongan  University aims to determine whether entrepreneurship courses have an impact on student interest in entrepreneurship after graduation  ,  the  results  of  the  study  concluded  that  85  %  chose  jobs  as  entrepreneurial  as preferred occupation, after college , before and after taking entrepreneurship courses, 52 % of students said that they chose jobs as entrepreneurial as affected entrepreneurship courses and the  remaining  48  %  is  not  due  to  the  effects  of  entrepreneurship  courses  because  of  other factors  ,  Asymp  value  .  Sig  .  (  2  -  tailed  )  of  0.00  thus  Ho  Denied  means  that  there  are differences  in  the  working  interest  before  and  seudah  students  taking  entrepreneurship courses  ,  it  can  be  seen  that  the  53%  who  chose  to  work  as  a  clerk  after  graduating  from college and moving interest as an entrepreneur after a entrepreneurship courses .. The Keywords : Entrepreneurship Course.  Interest,  Enterprenuer.